2017
DOI: 10.20900/jpbs.20170006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Schizophrenia

Abstract: Many studies show that oxidative stress is a pathophysiological mechanism of schizophrenia. Elevated oxidative stress levels and the damage to the antioxidant defense system can observed in early schizophrenia. High oxidation levels damage lipids, proteins, nucleic acids and other tissues. Antioxidant defense system imbalance has been observed in both neuroleptic-naïve first-episode schizophrenics and chronic schizophrenics being treated with medication and indicates the presence of oxidative stress in schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…Finally, the oxidative stress condition is notorious when there is a significant increase in lipid peroxidation levels only in plasma/serum samples. Our meta-analyses collaborate with the finding that the oxidant and antioxidant defense systems indicators have shown that antioxidant defense system defects reflect early pathophysiologic changes in schizophrenics 44 . But it should be noted that even performing sensitivity analyzes for all markers, it was not possible to reduce the heterogeneity of the results obtained.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Finally, the oxidative stress condition is notorious when there is a significant increase in lipid peroxidation levels only in plasma/serum samples. Our meta-analyses collaborate with the finding that the oxidant and antioxidant defense systems indicators have shown that antioxidant defense system defects reflect early pathophysiologic changes in schizophrenics 44 . But it should be noted that even performing sensitivity analyzes for all markers, it was not possible to reduce the heterogeneity of the results obtained.…”
Section: Discussionsupporting
confidence: 72%
“…These contradictory findings may be due, to some extent, to large differences between samples, including different evaluations and analytical methods and clinical factors that can alter oxidative stress levels parameters. Also, most of the studies provided MP-2021-447 insufficient information or not control for confounding factors such as body mass index, gender-based diferences, disease development stage and substance or tobacco use 44,45 . The family members' perception of what would be the FEP can also be a primary limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…O fato dos neurônios somente desenvolverem respiração aeróbia mitocondrial, com o agravante das células da glia defenderem as estruturas nervosas por meio da fagocitose, cria-se uma condição altamente favorável para alta produção de EROs e ERNs e de dano oxidativo ao tecido cerebral (MONICZEWSKI et al, 2015). O mecanismo de estresse oxidativo da esquizofrenia não é totalmente compreendido, mas cada vez mais evidências apoiam a hipótese de que tal condição desempenha um papel na fisiopatologia desta doença (HUANG;LIU, 2017).…”
Section: Discussionunclassified
“…Os sintomas são classificados em três categorias: sintomas positivos (por exemplo, delírios e/ou alucinações), sintomas negativos (embotamentos afetivos, alogias e/ou avolições) e disfunção cognitiva. A etiologia precisa da doença permanece obscura e ambos os fatores, genéticos e ambientais, parecem estar envolvidos (HUANG;LIU, 2017).…”
Section: Introductionunclassified
“…Meanwhile, the functions of serum antibodies with catalytic properties have been under active investigation in recent years. Oxidative stress is also an important factor for the initiation and progression of this disease, as evidenced by an imbalance in the antioxidant defense system in patients during the first episode and patients with chronic forms of schizophrenia receiving long-term antipsychotic treatment [ 8 , 9 , 10 ]. Disturbances of the redox balance in schizophrenia lead to alterations in various metabolic and signaling pathways, thereby eventually contributing to aberrant neuronal development, hypomyelination, immune system dysfunction, and the development of inflammatory processes [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%